Modern weapons and military equipment for issue 3-2015 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Images show North Korean vessel firing new SSM; India fires canister-launched Agni 5…and Pakistan tests Ra’ad; Iranian cruise missile unveiling raises questions about range; China starts work on first indigenous aircraft carrier; Local contender enters Emirati 8X8 race; Norinco unveils AR-3 MRL; Fortress mentality: Focus on anti-access coastal defences; Lighten up: a new generation of guided infantry missiles grows up.